Efficacy of three natural substances against apple aphid (Aphis pomi De Geer, Aphididae, Homoptera) under laboratory conditions - Žiga LAZNIK; Vlasta CUNJA; Milica KAČ; Stanislav TRDAN (Acta Agriculturae Slovenica, 2011)
In 2008 the efficacy of three environmentally friendly substances against apple aphid (Aphis pomi) was tested. The selected substances were cinnamic acid and two plant extracts, namely glicolic extract of comfrey (Symphytum officinale) and fluid extract of marigold (Calendula officinalis). All of the substances were tested at 0.5, 1 and 5 % concentrations. The individuals of apple aphids were collected in the organic orchard of the Biotechnical Faculty in Ljubljana; 10 aphids were then transferred to an apple tree leaf, which was previously sprinkled with water, treated with selected substance and put in a Petri dish. The efficacy was assessed at 15, 20 and 25 °C with relative humidity being 75 %. The mean corrected mortality rate was determined on the first, second and third day after treatment. In general all of the tested substances showed aphicidal properties, and the highest mean corrected mortality rates were determined on the third day at 25 °C. Only marigold extract exceeded a 50 % aphicidal efficacy at 15 °C and at 5 % concentration of the suspension used, while other treatments showed aphicidal efficacy between 4 ± 4 % (cinnamic acid, 15 °C, 0.5 %) and 39 %±12 % (cinnamic acid, 25 °C, 1 %). In general, the best mean efficacy (mean corrected mortality rate (15 % ± 2) % of the substances tested was found at highest concentration.